Communicating Genetics : Visualizations and Representations - Yu, Han (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book examines the visual representations used in the popular communication of genetics. Drawing upon public science communication theories, information design theories, and social semiotics, the book offers both in-depth analyses and high-level synthesis of how genetics is visualized for the U.S. public from the early 20th century to the present. Individual chapters focus on six visual genres: photographs, micrographs, illustrations, genetic code images, quantitative graphs, and molecular structure images. Han Yu challenges readers to consider the significance of these images we often take for granted, including their historical contexts, scientific backstories, information richness, stylistic choices, economic motivations, and social implications. In doing so, the book reveals the complex cognitive, affective, and social-cultural factors that both shape and are shaped by these images. The book will be particularly useful to scholars of public science communication and visual communication, practitioners of science communication, and scientists from a range of related life science disciplines.
Keywords: Social sciences.; Human genetics.; Life sciences.; Science education.; elektronické knihy; electronic books